Semen contact urticaria. - Poskitt, B; Wojnarowska, F; Shaw, S (1995)
An allergic reaction to human seminal fluid was first reported by Halpern et al. 1967. Since then there have been more than 30 cases recorded in the literature but it remains a rare cause of dyspareunia.